Update on gonadotropin-releasing hormone treatments for repeat breeders - Stevenson, Jeffrey S. (Kansas Agricultural Experiment Station, 2012)
In three of six studies involving over 1,650 cows, treatment of lactating dairy cows with 100 µg GnRH (2 cc Cystorelin®) at the time of third or fourth insemination improved conception rates by 12 percentage points. When all six studies are considered, rates improved by 10 percentage points. These data provide strong evidence for continued use of GnRH at the time of insemination for repeat breeders.
Keywords: Dairy; Gonadotropin-releasing hormone (GnRH); Conception rates; Lactation